GAMBARAN MENYIKAT GIGI TERHADAP TINGKAT KEBERSIHAN GIGI DAN MULUT PADA MURID KELAS V DI MIN 9 KECAMATAN ULEE KARENG KOTA BANDA ACEH - Linda Suryani (Biotik, 2017)
Oral and oral hygiene is a condition that is free of disorders that can affect the level of oral hygiene such as plaque and tartar. Brushing teeth can prevent the occurrence of food debris on the sidelines of teeth and tooth surfaces. Based on preliminary interviews on 10 children MIN 9 Banda Aceh, 7 of them frequency and time brushing teeth is not true, because they brush their teeth only in the morning when bathing in the morning only. From the preliminary examination conducted by the authors on 10 students, 6 of them had mean bad OHI-S (3.5), and 3 of them had average moderate OHI-S (1,3), and 1 of them had flat good OHI-S (0.8). This study aims to determine the description of toothbrushing to the level of oral hygiene in grade V students in MIN 9 Banda Aceh. This research is descriptive, conducted on 13 June to 14 June 2013. The population is 35 students MIN 9 Banda Aceh. The sample in this research is 35 students. The results showed that the dental and oral hygiene status in terms of tooth brushing frequency in the students of MIN 9 Banda Aceh City has OHI-S criteria being as many as 10 people (58.8%). While the status of dental and oral hygiene in terms of how to brush teeth on Elementary School students Lameu Sakti district Pidie has OHI-S criteria are as many as 9 people (56.3%). And dental and oral hygiene status in terms of brushing time on students MIN 9 Banda Aceh city has OHI-S criteria being as many as 10 people (58.8%). It can be concluded that students who brush once-daily teeth have moderate OHI-S criteria and students who brush their teeth in the morning bath also have moderate OHI-S criteria. It is suggested to students of MIN 9 Banda Aceh to pay more attention to oral hygiene.